ABSTRACT Unlocking Africa’s Demographic Dividend: A Pathway to Youth-Centric Public Policy and Entrepreneurial Ecosystems: 44th RTC (African Journal of Public Administration & Management, 2026)
Sub-Saharan Africa is home to the world’s youngest population, with over 60% under the age of 25. This demographic surge presents both an opportunity and a challenge. If effectively empowered, Africa’s youth could become a transformative engine for inclusive growth, innovation, and resilient governance. However, persistent gaps in access to skills, finance, markets, and public participation continue to marginalize young people from mainstream development processes.This paper interrogates the role of agile public administration in translating Africa’s demographic potential into tangible dividends. It draws from case studies in Kenya, Rwanda, and Ghana to analyze how targeted youth empowerment strategies—particularly in digital entrepreneurship, agribusiness incubation, and civic-tech platforms—can drive structural transformation. The paper adopts the CEPA principles of effectiveness, accountability, and inclusivity as a framework to assess public sector interventions aimed at youth engagement.Using a mixed-methods approach, the research highlights policy bottlenecks, institutional innovations, and partnership models that have proven effective in enabling youth-led change. The study concludes by proposing a multi-stakeholder roadmap for governments, civil society, and private actors to mainstream youth as co-creators in development. By reimagining public administration through a youth lens, Africa can harness its demographic dividend to achieve citizen-centric and future-proof governance.Keywords: Youth Empowerment, Demographic Dividend, Public Administration, Digital Inclusion, CEPA Principles, Sub-Saharan Africa